Employers Perspective Towards People with Disability Using Disability Confidence Framework Study Case: Contact Center at Sparkling Indonesia & Bank Masa Depan - Rendar Mahardhika Putra; Riani Rachmawati (CCIT (Creative Communication and Innovative Technology) Journal, 2024)
Issues towards diversity, equity, and inclusion currently become a main focus and big agenda both for government and corporate. One of the inclusion strategy encouraged by employers in corporate world is the inclusion towards people with disability at the workplace. The current problem, many employers lack of disability confidence knowledge, means that how the employers enhancing their understanding about people with disability, removing all barriers, and created a strong business case for hiring people with disability and deliver a significant impact at the workplace. Therefore, an exploratory study required to be conducted with the scope of two companies who has world-class contact center and also become a pioneer or role model in terms of their lead towards disability employment in contact center industry. In collecting the data, this study conducted semi structured in depth interviews with ten informant as the representative of the management, with qualitative thematic analysis methodology. The results came up from this study stated that employer’s broadened perspective, employer’s full support, and disability confidence or the employer’s confident level in hiring and employed people with disability are the important factors to create disability inclusion is truly happened at the workplace.